Diversity, use and production of farmers’ varieties of common bean (Phaseolus vulgaris L., Fabaceae) in southwestern and northeastern Ethiopia - Abera, B.; Berhane, M.; Nebiyu, A.; Ruelle, M.L.; McAlvay, A.; Asfaw, Z.; Abebe, A.T.; Woldu, Z. (Springer, 2020)
Legumes are a critical component of many agricultural systems and a major contributor to global food systems. Common bean (Phaseolus vulgaris L.) is the most widely grown legume crop in Ethiopia. It is an important source of food, income, and soil fertility management in southwestern (SW) and northeastern (NE) Ethiopia, and used as medicine, fodder, and honeybee forage in the NE. Diversity and use of farmers’ varieties of common bean (Phaseolus vulgaris) bean were investigated in five administrative zones in SW and NE Ethiopia. Structured and semi-structured interviews were conducted with 288 general informants and 48 key informants in five agroecological zones inhabited by four cultural groups. Thirty-nine varieties were identified based on farmers’ naming practices. Varietal richness and diversity were found to be highest in the humid, tepid mid-highlands of Kefa (13) and Bench Maji and Sheka (12). However, farmers in both research areas typically plant only one or two varieties. Interestingly, the number of varieties per household was highest (2.3) in South Wollo Zone of the NE, where only six varieties were found. We find that varieties per household are limited by small landholdings in the SW and varietal richness in the NE. Given these limitations, policies and programs to conserve varietal diversity and increase productivity are more likely to be effective if organized at the community level in the SW and the household level in the NE. Agromorphological and genetic characterization of common bean varieties would facilitate the management and conservation of their diversity as a source of resilience.